PEMANFAATAN TEKNOLOGI DIGITAL DALAM LAYANAN BIMBINGAN KLASIKAL UNTUK MEMANTAPKAN MINAT KARIR ANAK TUNARUNGU - Pardi, Pardi; Fitri, Susi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The integration of digital technology in education, particularly for deaf students, has become an imperative. In this digital age, educators must possess digital competencies to craft engaging and effective learning environments. Nearpod, a web-based platform offering various interactive features, stands as a viable solution. This article explores Nearpod's application in classical guidance services to bolster career interests among deaf students. Nearpod facilitates unique interactions between educators and students through features like interactive slides, gamification, and direct questioning. Deaf students can access learning materials and complete tasks directly through features like Collaborate Board and interactive quizzes. The process involves tailored steps, with guidance counselors preparing lesson themes and delivering content through Nearpod. The platform also streamlines assessment and evaluation through its reporting feature. Through Nearpod's utilization, classical guidance services for deaf students can become more effective in nurturing career interests, while aiding educators in designing engaging learning experiences.